Glicerina na alimentação de bovinos de corte: Consumo, digestibilidade, parâmetros ruminais e sanguíneos - Fávaro, Vanessa Ruiz [UNESP]; Ezequiel, Jane Maria Bertocco [UNESP]; D'Aurea, André Pastori [UNESP]; Van Cleef, Eric Haydt Castello Branco; Sancanari, Juliana Borsari Dourado [UNESP]; Santos, Viviane Correa [UNESP]; Homem, Antonio Carlos [UNESP] (Universidade Estadual de Londrina, 2015)
This study aimed to evaluate the effects of glycerin supplements in the diet of beef cattle by assessing intake, apparent nutrient digestibility, ruminal pH, ruminal ammonia concentrations, and blood parameters. The study was conducted at the São Paulo State University (UNESP, Jaboticabal campus) using five crossbred cattle in an experiment employing a 5 × 5 Latin square design. Cattle diet treatments included zero, 50, 100, 150, and 200 g kg-1 dry matter of glycerin. Feed, leftover feed, and faeces were collected to determine intake and digestibility. Samples of ruminal liquid were collected at -1, 0, 1, 2, 4, 6 and 8 h after feeding to determine pH and ruminal ammonia. Blood was collected four hours after the morning feeding from the coccygeal vein. Replacing maize with glycerin resulted in lower concentrations of ether extract and non-fibre carbohydrates in the diets, leading to a linear decrease in the intake of these nutrients (P<0.05). The digestibility of neutral detergent fibre and nonfibre carbohydrates also decreased linearly with increasing dietary glycerin concentrations (P<0.05). The results for ruminal fermentation parameters showed a linear decrease (P<0.05) in the ruminal concentration of N-NH3 with increasing dietary levels of glycerin; however, ruminal pH was not affected (P>0.05). Serum concentrations of urea, triglycerides, cholesterol, and plasma glucose concentrations were within normal ranges based on the literature. The inclusion of glycerin in the cattle diet altered rumen fermentation, reducing the concentration of N-NH3, the digestibility of neutral detergent fiber and non-fiber carbohydrates.
Glycerin in cattle feed: Intake, digestibility, and ruminal and blood parameters
Keywords: Beef cattle; Biodiesel; Glycerin; Metabolism; Ruminal fermentation